Culture-Dependent Bioprospecting of Bacterial Isolates From the Canadian High Arctic Displaying Antibacterial Activity - Marcolefas, Evangelos; Leung, Tiffany; Okshevsky, Mira; McKay, Geoffrey; Hignett, Emma; Hamel, Jérémie; Aguirre, Gabriela; Blenner-Hassett, Olivia; Boyle, Brian; Lévesque, Roger C.; Nguyen, Dao; Gruenheid, Samantha; et al. (Frontiers in Microbiology, 2019)
The goal of this study was to isolate, screen, and characterize Arctic microbial isolates from Expedition Fjord, Axel Heiberg Island, Nunavut, Canada capable of inhibiting the growth of foodborne and clinically relevant pathogens. Arctic bacteria were isolated from twelve different high Arctic habitats pertaining to active layer permafrost soil, saline spring sediments, lake sediments, and endoliths. This was achieved using (1) the cryo-iPlate, an innovative in situ cultivation device within active layer permafrost soil and (2) bulk plating of Arctic samples by undergraduate students that applied standard culturing. To mitigate the possibility of identifying isolates with already-known antibacterial activities, a cell-based dereplication platform was used. Ten out of the twelve Arctic habitats tested were found to yield cold-adapted isolates with antibacterial activity. Eight cold-adapted Arctic isolates were identified with the ability to inhibit the entire dereplication platform, suggesting the possibility of new mechanisms of action. Two promising isolates, initially cultured from perennial saline spring sediments and from active layer permafrost soil (Paenibacillus sp. GHS.8.NWYW.5 and Pseudomonas sp. AALPS.10.MNAAK.13 respectively), displayed antibacterial activity against foodborne and clinically relevant pathogens. Paenibacillus sp. GHS.8.NWYW.5 was capable of inhibiting methicillin resistant and susceptible Staphylococcus aureus (MRSA and MSSA), Listeria monocytogenes, Salmonella enterica and Escherichia coli O157:H7. Pseudomonas sp. AALPS.10.MNAAK.13 was observed to have antagonistic activity against MRSA, MSSA, Acinetobacter baumanii, Enterococcus faecium, and Enterococcus faecalis. After whole genome sequencing and mining, the genome of Paenibacillus sp. GHS.8.NWYW.5 was found to contain seven putative secondary metabolite biosynthetic gene clusters that displayed low homology (<50% coverage, <30% identity, and e-values >0) to clusters identified within the genome of the type strain pertaining to the same species. These findings suggest that cold-adapted Arctic microbes may be a promising source of novel secondary metabolites for potential use in both industrial and medical settings.